Служба приватного сыска. Травля лисы - Константинов Андрей (Русский проект, 2002)
Экземпляры: (20190402) / Инвентарный номер: 37127 / Цена: 51.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К 65 / ББК: 84(2Рос=Рус)6